High power modular converters for grid interface applications - Jankovic, Marija (2017)
Scientists at European Organization for Nuclear Research (CERN) are currently conducting feasibility studies for the Compact linear collider (CLIC); their proposed next experimental setup for gathering information on the fundamental particles of matter. This experiment will involve the simultaneous pulsing of 1300 klystron modulators to produce a 140us, 39GW pulse with a 50 Hz repetition rate. This proposal presents many demands for the connected power system as an effort is made to "hide" this pulse from the local distribution network - instead drawing only the constant average power of approximately 300MW. This challenge is considered in this work. In order to understand the optimal approach both the power system architectures and power electronics interfaces must be considered simultaneously. An approach to the optimisation of the power system architecture is described in this thesis. It is clear from this exercise that the optimum power converter topology for the interface between the electricity distribution network and the klystron modulators is the Modular Multilevel Converter (MMC). This converter is mainly used in modern HVDC transmission circuits as a result of its high efficiency and ability to produce high quality AC waveforms. Pulsing of the klystron modulators does however create further challenges for the inner control loops of an MMC. The placement of the pulse can create imbalances in the DC capacitors of the MMC submodules which may result in tripping of the converter if not corrected. This thesis proposes three arm balancing solutions to be applied together with the decoupled AC and DC side controller designed for the specified application. These proposed solutions to the aforementioned problems are successfully validated using simulation work in PLECS and using data from a laboratory scale prototype of one of the MMC interface power converters.